Mapping the Minds of Gen Z: The Dynamics of Brand Loyalty in Indonesia - Azizi, Wafiq Nuril; Raharjo, Raden Johnny (PT FORMOSA CENDEKIA GLOBAL, 2024)
This journal reviews aspects of Generation Z's loyalty to local brands, emphasizing psychographic analysis. The research method used is qualitative, using in-depth interviews with Generation Z individuals who show interest and loyalty to local brands. By referring to consumer behavior theory, especially psychographic theory, this research identifies internal and external factors that encourage Generation Z to choose and remain loyal to local brands. The research results provide a deep understanding of consumer motivation, personal values, personality, cultural and social influences, and decision-making processes that shape Generation Z consumer behavior towards local brands